Regulatory gaps on single-use plastics in different regional contexts - Macías Reyes, Maria Delia; Mejía Baque, Diana Stefanía (Frónesis, 2022)
The scientific, technological and commercial advancement of society has been based on the invention and development of materials that improve their quality of life. Among these materials, we find the so-called single-use plastics, which have become protagonists in our daily lives with an increasingly accelerated and constant production, sale and use. The facilities that arise from single-use plastics allow their use to be indiscriminate, which in turn generates consequences for human health, the environment and the economy. For this reason, it is imperative that the law addresses the regulatory gaps on the production, sale and use of single-use plastics, as well as the experiences in the attempt to regulate this problem in different regional contexts on a global scale. This study addresses the regulatory gaps in the production, sale, and use of single-use plastics in the regional contexts of the Americas, Asia-Pacific, Europe, and the Middle East-Africa. The study critically reviews the literature on scientific and normative criteria of the effects that plastics have had on human health, the environment, the economy and the law.